(untitled) (Zoological Records and Reviews, 2024)
Agricultural intensification remains the dominant driver of animal biodiversity loss in European farmland landscapes, yet the relative importance of specific management practices – pesticide application, fertilisation intensity, tillage regime, crop diversity, and structural element retention – varies among taxa and regions. This study quantifies the independent and combined effects of six agricultural practice parameters on four animal groups (carabid beetles, breeding birds, small mammals, and farmland butterflies) across 96 paired conventional and agri-environment scheme (AES) farm plots in Spain, the Netherlands, and Austria (n = 22,847 individual records across 318 taxa, 2021-2023). Pesticide application index (PAI) was the strongest negative predictor of carabid beetle diversity (GLMM beta = -0.62 +- 0.09, p < 0.001) and butterfly richness (beta = -0.54 +- 0.08, p < 0.001). Fertilisation intensity (nitrogen application > 120 kg N/ha/yr) significantly reduced sward structural complexity, indirectly suppressing breeding bird diversity by 28.4 +- 5.8% (mediation analysis; p < 0.001). Crop diversity (Shannon index of crop types within 500 m) was the strongest positive predictor of breeding bird richness (beta = +0.48 +- 0.08, p < 0.001). AES plots with wildflower margins, reduced tillage, and pesticide restrictions supported 42.4 +- 6.8% higher mean species richness than adjacent conventional plots across all four animal groups. The biodiversity benefit of AES was significantly moderated by landscape context: AES plots embedded in low-diversity landscapes (< 20% semi-natural habitat within 2 km) showed 64.8% lower biodiversity benefit than those in heterogeneous landscapes. These findings provide an empirical basis for optimising CAP Eco-scheme design to maximise biodiversity outcomes per unit programme expenditure.